Loose Talk, Scale Presuppositions and QUD - Hoek, Daniel (Proceedings of the Amsterdam Colloquium, 2019)
I present a new pragmatic theory of loose talk, focussing on the loose use of numbers and measurement expressions. The account explains loose readings as arising from a pragmatic mechanism aimed at restoring relevance to the question under discussion (QUD), appealing to Krifka’s notion of a measurement scale [7]. The core motivating observation is that the loose reading of a claim need not be weaker than its literal content, as almost all pragmatic treatments of loose talk have assumed (e.g. Lasersohn [10]). The loosening mechanism described here can be applied to a range of other linguistic phenomena as well.